Enhanced methanogenic performance and metabolic pathway of high solid anaerobic digestion of chicken manure by Fe2+ and Ni2+ supplementation. (1st July 2019) - Bi, Shaojie; Westerholm, Maria; Qiao, Wei; Mahdy, Ahmed; Xiong, Linpeng; Yin, Dongmin; Fan, Run; Dach, Jacek; Dong, Renjie
Highlights: Fe 2+ and Ni 2+ enhanced long term methanogenic performance at TAN of 6.8/L. Both acetoclastic and hydrogenotrophic methanogenic activity was increased. The microbial communities was identified by high throughout sequencing. Hydrogenotrophic methanogens were out-competed with trace elements addition. Abstract: High solid anaerobic digestion (AD) is a promising technology for the treatment of organic waste in terms of efficient bioenergy production and digestate volume reduction. However, the high solid AD of chicken manure has been a challenge due to the inhibition effects caused by high ammonia levels. In this study, the addition of 280 mg/L Fe 2+ and 2 mg/L Ni 2+ has been proven to enhance the microbial activity and to overcome inhibition under the stressed environment. The mesophilic digesters feeding with total solid around 150 g/kg operated at an organic loading rate of 4.8 g/(L d) based on volatile solid and a 20-day hydraulic retention time. The total ammonia-nitrogen reached around 6.8 g/L in control and Fe-Ni digesters. The results from the 147-day continuously-fed experiment provided an increment of 34% methane production and a 29% reduction of volatile fatty acids against control. The acetoclastic and hydrogenotrophic methanogenic activity was increased by 89% and 40% respectively. The high throughout sequencing results showed an increased percentage of Methanosarcina sp., which may have contributed to the shifting of the methanogenic pathway towards acetoclastic methanogenesis. The positive effects of Fe 2+ and Ni 2+ supplementation obtained in this study lay the foundation for its use in AD of nitrogen rich materials.